Identifying the challenges impacting water resources management caused by various stakeholders in the rural tourism setting in Malaysia - Prabhakaran, Sudesh; Nair, Vikneswaran; Ramachandran, Sridar (2012)
Despite having many policies and government agencies to monitor the quality and quantity of water resources, the level of pollution has reached a very alerting stage due to the inadequate enforcement and policy implementation by the authorities in the rural tourism spots. The development of rural areas for tourism and its activities has caused water resources pollution and degradation to increase. The aim of this study is to identify the challenges impacting the water resources management in terms of quantity and quality caused by the various stakeholders in the rural tourism setting in Malaysia. This paper will primarily endow with a discussion on the probable impacts of rural tourism on the water resource management. It will be followed by a discussion on the four main paradigms and the use of critical realism and the stakeholder’s theory to view this research to make the assumptions and interpretations.